Extending the General Theory of Crime to “The East:” Low Self-Control in Japanese Late Adolescents - Vazsonyi, Alexander Thomas (Journal of quantitative criminology, 2004)
This study examined the measurement of low self-control as well as the low self-control-deviance relationship in a sample of N = 335 Japanese late adolescents. Participants completed the Grasmick et al. low self-control instrument and the Normative Deviance Scale (NDS). Findings indicated that the low self-control measure was a valid and reliable indicator of low self-control among male and female Japanese late adolescents and that it was multi-dimensional. Furthermore, the study provided evidence that low self-control was consistently related to diverse measures of deviance, ranging from trivial to more serious norm-violating behaviors (e.g., assault). Finally, in a series of comparisons of partial unstandardized regression coefficients between Japanese and U.S. late adolescents, the study found that the low self-control-deviance relationship was invariant across all measures of deviance with the exception of alcohol use. Findings are discussed in terms of their importance for cross-cultural/cross-national predictions made by the General Theory of Crime.